Composite membrane with salt dirt gradient separation and catalytic evaporation functions as well as preparation method and application of composite membrane

By constructing a gradient pore structure on the electrospun fiber membrane and loading catalytic properties, a salt-fouling gradient separation and catalytic evaporation sequence membrane was prepared, which solved the wetting, pollution and scale problems of traditional hydrophobic membranes in high-salt wastewater treatment, and achieved efficient salt and pollutant interception.

CN120550651APending Publication Date: 2025-08-29NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510683023.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

Traditional hydrophobic membranes are prone to wetting, contamination and scaling during the treatment of high-salt wastewater, and are difficult to effectively intercept volatile organic pollutants, resulting in unstable treatment capacity.

Method used

The ultra-thin dense cortex was prepared on the electrospun fiber membrane by vacuum-assisted filtration technology, and the gradient pore structure was constructed and catalytic performance was loaded to form a salt-fouling gradient separation and catalytic evaporation sequence membrane.

Benefits of technology

It realizes efficient gradient sequestration of salts and pollutants, maintains high membrane flux, and solves multiple technical problems of traditional membrane materials in high-salt wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120550651A_ABST
    Figure CN120550651A_ABST
Patent Text Reader

Abstract

The invention discloses a composite film with salt-dirt gradient separation and catalysis functions for a hot-method membrane desalination process, and a preparation method and application of the composite film. The composite membrane adopts a three-layer structure design, sequentially comprises a separation layer, a catalyst layer and an evaporation layer from top to bottom, and can be effectively applied to treatment of complex industrial high-salinity wastewater. The specific application method is as follows: the direct contact type membrane separation device is used for concentrating the industrial high-salinity wastewater. According to the preparation method, an electrostatic spinning fiber membrane is innovatively adopted as a substrate, and the gradient separation-catalysis-evaporation sequential membrane with an ultrathin compact skin layer is constructed through a vacuum-assisted filtration technology. The composite membrane can simultaneously realize high-efficiency gradient interception and catalytic degradation functions of salt dirt in a hot-method membrane separation process, keeps relatively high membrane flux, effectively solves the common problems of membrane wetting, scaling and the like in the hot-method membrane separation process, and breaks through the technical bottleneck that volatile organic pollutants are difficult to synchronously intercept in a traditional membrane distillation technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of separation membrane preparation, relates to an organic-inorganic composite membrane, and specifically relates to a membrane with a salt-pollution gradient separation-catalysis-evaporation sequence structure, and a preparation method and application thereof. Background Art

[0002] With the rapid development of industrial production and desalination, the discharge of high-salinity wastewater continues to rise. If discharged untreated, this wastewater can cause a series of environmental problems, including water mineralization, soil salinization, and eutrophication, posing a serious threat to the ecological environment and human health. Against this backdrop, the advanced treatment and resource utilization of high-salinity wastewater has become a major issue that needs to be addressed urgently. Membrane distillation (MD) technology has attracted considerable attention due to its ability to achieve high water recovery rates using low-grade heat sources. This technology utilizes the vapor pressure differential generated by the temperature difference across the membrane to drive water vapor through the membrane pores and condense on the cold side. With its significant advantages, such as high salt rejection, simple system, and high recovery rates, it has shown great potential in the treatment of high-salinity wastewater. However, the high salinity and complex composition of high-salinity wastewater pose significant challenges to traditional membrane distillation technology. On the one hand, volatile pollutants can penetrate the membrane pores along with the water vapor, seriously affecting the water quality of the product. On the other hand, traditional hydrophobic membranes are prone to wetting, fouling, and scaling, and are unable to effectively retain volatile organic compounds, limiting the stability of treatment results. Although thin-film composite (TFC)-hydrophobic Janus composite membranes achieve efficient separation of water and non-volatile pollutants through their dense hydrophilic TFC layer, the hydrophilic layer not only increases water mass transfer resistance, resulting in a decrease in flux, but can also exacerbate the permeation of volatile pollutants within the membrane, similarly affecting effluent quality. Therefore, the development of new membrane materials that can simultaneously and efficiently separate water from volatile / non-volatile pollutants has important scientific significance and application value. Summary of the Invention

[0003] In response to the problems of membrane wetting, contamination and scaling faced by traditional hydrophobic membranes in the process of treating high-salt wastewater, as well as technical bottlenecks such as difficulty in effectively intercepting volatile organic pollutants resulting in unstable treatment capacity, the present invention provides a composite membrane with salt-pollution gradient separation and catalytic evaporation functions, as well as its preparation method and application. Specifically, the present invention uses vacuum-assisted filtration technology on electrospun fiber membranes to prepare a gradient separation-catalysis-evaporation sequence membrane with an ultra-thin and dense cortex. This composite membrane can not only achieve efficient gradient interception of salt and pollutants simultaneously during the membrane distillation process, but also maintain a high membrane flux (such as Figure 1 As shown in the figure, it effectively solves the multiple technical difficulties of traditional membrane materials in wastewater treatment.

[0004] The purpose of the present invention is achieved through the following technical solutions: A composite membrane with salt-pollution gradient separation and catalytic evaporation functions comprises, from top to bottom, a separation layer, a catalytic layer and an evaporation layer, wherein: the evaporation layer is an electrospun fiber membrane, the catalytic layer is an organic-inorganic composite film, and the separation layer is an organic or inorganic layer.

[0005] A method for preparing the composite membrane having the functions of salt-contamination gradient separation and catalytic evaporation comprises the following steps: Step 1: Add a hydrophobic polymer to a solvent, heat and stir in a water bath, and then gradually cool to room temperature to obtain a base membrane spinning solution, and prepare an electrospun fiber membrane by continuously electrospinning the base membrane spinning solution, wherein: The hydrophobic polymer is one or more of polyvinylidene fluoride, polyethersulfone, and polyurethane; The solvent is one or more of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone; The mass ratio of the hydrophobic polymer to the solvent is 5-20:100; A conductive agent is also added to the solvent, and the mass ratio of the conductive agent to the hydrophobic polymer is 0.1-0.5:100; The conductive additive is one or more of lithium chloride, sodium chloride and calcium chloride; The water bath heating temperature is 60-150°C, and the stirring time is 3-5 h; The continuous electrospinning process requires transferring 5-15 mL of spinning solution from four needles to an electrospinning machine and performing electrospinning in a closed environment at 20-30°C and 35-75% relative humidity. In addition, the needle tip and the ground collector are positively and negatively charged, respectively, with a positive voltage of 10-40 kV and a negative voltage of 0-10 kV. The distance between the needle tip and the receiver is 10-30 cm, and the injection speed is 0.1-0.2 mm min. -1 , receiving speed is 30~50 r min -1 After the spinning solution is sprayed, the prepared membrane is peeled off from the aluminum foil to obtain the electrospun fiber membrane; Step 2: sandwiching the electrospun fiber membrane in step 1 between two glass plates and treating it under hot pressing at 100-200°C and 1-5 MPa for 1-6 hours to obtain a base membrane; Step 3: Preparation of amino-functionalized one-dimensional tubular or two-dimensional sheet material: 1-3 g of the one-dimensional tubular or two-dimensional sheet material is immersed in a hydrochloric acid solution for 12-36 hours, washed and dried, and then added to a solvent with 3-aminopropyltriethoxysilane and refluxed for 2-4 hours, washed and dried to obtain an amino-functional one-dimensional tubular or two-dimensional sheet material, wherein: The concentration of the hydrochloric acid solution is 1~3 mol L -1 ; The mass volume ratio of the amino-functionalized one-dimensional tubular or two-dimensional sheet material to 3-aminopropyltriethoxysilane is 1-5 g: 1-5 mL; The solvent is toluene; Step 4: Preparation of S-TpPa@amino-functionalized one-dimensional tubular or two-dimensional sheet material heat-resistant glass tube: The amino-functionalized one-dimensional tubular or two-dimensional sheet material prepared in step 3 is placed in a solvent with trialdehyde phloroglucinol (Tp) and 2,5-diaminobenzenesulfonic acid (Pa-SO3H) for ultrasonic treatment. After degassing, the reaction is carried out at 100-200°C for 2-4 days. The precipitated product is then collected by filtration, washed, and Soxhlet extracted. The product is dried to obtain S-TpPa@amino-functionalized one-dimensional tubular or two-dimensional sheet material heat-resistant glass tube, wherein: The one-dimensional tubular material is a carbon nanotube; The two-dimensional sheet material is graphene oxide, MXene, molybdenum disulfide or other two-dimensional sheet materials; The ultrasonic treatment time is 20 to 60 min; The number of degassing is 2 to 4 times; The drying temperature is 40-80°C and the drying time is 12-36 hours; The molar concentration ratio of the amino-functionalized one-dimensional tubular or two-dimensional sheet material, Tp and Pa-SO3H is 0.2~2:1:1~2; The solvent is one or more of n-butanol, isopropanol, acetic acid, and o-dichlorobenzene mixed solvent; Step 5: Preparation of S-TpPa@amino-functionalized one-dimensional tubular or two-dimensional sheet material-Co: The product of step 4 is ultrasonically placed in anhydrous dichloromethane, followed by addition of cobalt acetate and stirring. After the reaction, the solid is collected by filtration and repeatedly washed with dichloromethane and ethanol to completely remove uncoordinated metal salts and organic residues. The solid is vacuum dried to obtain the final product S-TpPa@amino-functionalized one-dimensional tubular or two-dimensional sheet material-Co, wherein: The ratio of the S-TpPa@amino-functionalized one-dimensional tubular or two-dimensional sheet material, anhydrous dichloromethane and cobalt acetate is 50-100 mg: 20-50 mL: 50-70 mg; The stirring time is 12 to 36 hours; The vacuum drying temperature is 30-60°C and the time is 10-20 h; Step 6: Prepare a dispersion of one-dimensional tubular or two-dimensional sheet materials with catalytic properties: Weigh 1-20 mg of the one-dimensional tubular or two-dimensional sheet material, add it to ultrapure water and disperse it ultrasonically. Then, add 50-100 mg of the final product of step 5, stir it, and then disperse it ultrasonically to obtain a dispersion of one-dimensional tubular or two-dimensional sheet materials with catalytic properties, wherein: The one-dimensional tubular material is a carbon nanotube; The two-dimensional sheet material is graphene oxide, MXene, molybdenum disulfide or other two-dimensional sheet materials; The ultrasonic dispersion speed is 100-500 rpm and the time is 5-15 min; The stirring time is 0.5 to 3 h, and the ultrasonic time is 15 to 60 min; Step 7: vacuum filter the solution in step 6 onto the base membrane obtained in step 2 under a negative pressure of 0.75-2 MPa to obtain a catalytic layer; Step 8: 5-20 mL of a 100-1000 ppm one-dimensional tubular or two-dimensional sheet material dispersion is vacuum filtered onto the catalytic layer obtained in step 7 under a negative pressure of 0.75-2 MPa, and then dried in a forced air drying oven to obtain a separation-catalysis-evaporation sequential membrane, wherein: The one-dimensional tubular material is a carbon nanotube; The two-dimensional sheet material is graphene oxide, MXene, molybdenum disulfide or other two-dimensional sheet materials; The drying temperature is 60-120° C. and the drying time is 10-60 min to ensure that the moisture in the separation-catalysis-evaporation structure membrane is fully dried.

[0006] The composite membrane prepared by the above preparation method can be used in the treatment of complex high-salt wastewater. The specific application method is as follows: industrial high-salt wastewater is concentrated using a direct contact membrane separation device.

[0007] Compared with the prior art, the present invention has the following advantages: The present invention addresses the problems of membrane wetting, contamination and scaling faced by traditional hydrophobic membranes in the process of treating high-salt wastewater, as well as the difficulty in effectively retaining volatile organic pollutants, and the inability to achieve stable and efficient treatment capabilities. A new method for preparing ultra-thin and dense composite membranes on the surface of distillation membranes using vacuum-assisted filtration technology is proposed. This method constructs a gradient pore structure on the surface of the distillation membrane and loads catalytic properties to obtain a membrane with salt-pollution gradient separation and catalytic evaporation sequence, which effectively solves the wetting and scaling problems and the retention problem of volatile organic pollutants in the membrane distillation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 Schematic diagram of separation, catalysis and evaporation of the separation-catalysis-evaporation sequence membrane.

[0009] Figure 2 Transmission electron microscope images of carbon nanotubes (left) and composite materials (right).

[0010] Figure 3 Scanning electron microscope images of carbon nanotubes (left) and composite materials (right).

[0011] Figure 4 This is a scanning electron microscope image of the graphene oxide separation layer.

[0012] Figure 5 This is a comparison chart of the water flux performance of the separation-catalysis-evaporation sequence membrane, the single-component evaporation membrane and the separation-evaporation membrane.

[0013] Figure 6 This is a comparison chart of the aniline removal rate performance of the separation-catalysis-evaporation sequence membrane, the single-component evaporation membrane and the separation-evaporation membrane. DETAILED DESCRIPTION

[0014] The technical solution of the present invention is further described below with reference to the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the scope of protection of the present invention. Example 1

[0015] This embodiment provides a method for preparing a membrane with a salt-contamination gradient separation catalytic evaporation structure, the method comprising the following steps: Step 1: Prepare base membrane spinning solution: Weigh 61.53 g of N,N-dimethylacetamide, then weigh 0.77 g of 1% mass fraction LiCl solution (solvent is N,N-dimethylacetamide), and finally weigh 7.7 g of polyvinylidene fluoride and add them to the above solvent. Stir the mixture vigorously at 60°C for 4 hours, and then gradually cool it to room temperature to obtain the base membrane spinning solution.

[0016] Step 2: Take 4 10 mL syringes and draw 10 mL of basement membrane spinning solution for electrospinning. Then, replace 4 10 mL syringes and draw 5 mL of basement membrane spinning solution for secondary spinning to obtain electrospun fiber membrane. The electrospinning process should always be maintained in a closed environment at 25°C and 70±2% relative humidity. The distance between the needle and the receiver is 20 cm, and the injection speed is 0.15 mm min. -1 , receiving speed is 30 r min -1 The needle tip and ground collector are applied with high voltage of +35kV and -5kV respectively.

[0017] Step 3: The fiber membrane obtained in step 2 is sandwiched between two glass plates, fixed with clips on all sides of the glass plates, and treated at 160°C and 3 MPa under hot pressing for 1 h to obtain a base membrane.

[0018] Step 4: Preparation of amino-functionalized carbon nanotubes: First, 2 g of carbon nanotubes (CNTs) were immersed in 1 mol L -1 The CNTs were acidified in a hydrochloric acid solution for 24 hours, then washed several times with ethanol and dried under vacuum. One gram of the treated CNTs was added to 100 mL of toluene solvent along with 0.5 mL of 3-aminopropyltriethoxysilane (APTES) and allowed to react under reflux for 3 hours. After the reaction, the product was washed with ethanol and dried under vacuum to obtain amino-functionalized carbon nanotubes (CNT-NH2).

[0019] Step 5: Synthesis of S-TpPa@CNT: Tp (21 mg, 0.1 mmol), Pa-SO3H (28 mg, 0.15 mmol), and CNT-NH2 (40 mg) were placed in a Pyrex tube. A 1:1 (v / v) n-butanol / o-dichlorobenzene mixture (2 mL) and 6 M acetic acid (0.2 mL) were added. The mixture was sonicated for 30 minutes, then rapidly frozen in liquid nitrogen and degassed by three freeze-pump-thaw cycles. The tube was sealed and reacted at 120°C for 3 days. After completion of the reaction, the precipitated product was collected by filtration, washed sequentially with dimethylacetamide and acetone, and Soxhlet extracted with tetrahydrofuran for 24 hours. The final product was dried in vacuo at 60°C for 24 hours to obtain S-TpPa@CNT as a dark red powder.

[0020] Step 6: Synthesis of S-TpPa@CNT-Co: The pre-synthesized S-TpPa@CNT (50 mg) was dispersed in 30 mL of anhydrous dichloromethane (CH2Cl2) and thoroughly dispersed by sonication for 10 min. Cobalt acetate (Co(CH3COO)2, 0.06 g, 0.27 mmol) was then added, and the mixture was stirred at room temperature for 24 h. After completion of the reaction, the solid product was collected by vacuum filtration and repeatedly washed with dichloromethane (3 × 10 mL) and ethanol (3 × 10 mL) to completely remove uncoordinated metal salts and organic residues. The resulting deep red solid product was vacuum dried at 40°C for 12 h to obtain the target composite material, S-TpPa@CNT-Co.

[0021] Step 7: Prepare a dispersion of graphene oxide loaded with catalytic properties: First, weigh 1.25 mg of graphene oxide and add it to 50 mL of ultrapure water, and ultrasonically disperse it for 15 minutes. Then, add 2 mg of the final product of step 6 and stir it for 1 hour. Ultrasonicate it for 30 minutes to evenly disperse it to obtain a dispersion of a two-dimensional layered material with catalytic properties.

[0022] Step 8: The two-dimensional layered material dispersion in step 7 is vacuum filtered onto the base film obtained in step 3 under a negative pressure of 0.75 MPa to obtain a composite film.

[0023] Step 9: Weigh 250 mg L -1 5 mL of the concentrated graphene oxide dispersion was vacuum filtered onto the composite membrane described in step eight under a negative pressure of 0.75 MPa, and then placed in a forced air drying oven at 100°C for 60 min to obtain a membrane with a salt-contamination gradient separation-catalysis-evaporation sequence.

[0024] The salt-contamination gradient separation-catalysis-evaporation membrane prepared in this example was used to distill high-salinity wastewater containing 20 ppm aniline. The parameters were set as feed side temperature of 60°C, permeate side temperature of 40°C, and flow rate of 240 mL min. -1 The volume of water collected per minute on the distillation side was recorded using an electronic balance, and the conductivity of the water on the distillation side was monitored using a conductivity meter to record the effluent quality. The composite membrane had a retention rate of up to 99.21% for high-salinity wastewater containing 20 ppm of aniline.

[0025] The transmission electron microscope and scanning electron microscope of steps 4 and 6 of this embodiment are as follows Figure 2 and Figure 3 As shown, the scanning electron microscope image of the graphene oxide separation layer is as follows Figure 4 As shown in the figure, this method successfully loaded catalytic properties on carbon nanotubes to obtain a membrane with salt-pollution gradient separation-catalysis-evaporation sequence, and its performance is as follows Figure 5 and Figure 6 shown. Example 2

[0026] This embodiment provides a method for preparing a catalytic evaporation membrane with a salt-contamination gradient separation function, the method comprising the following steps: Step 1: Prepare base membrane spinning solution: weigh 60 g of N,N-dimethylacetamide, then weigh 10 g of polyethersulfone, add the above solvent, heat in a water bath at 80°C and stir until mixed, to obtain a solution as the base membrane spinning solution, and obtain the base membrane spinning solution.

[0027] Step 2: Take 4 10 mL syringes and draw 10 mL of basement membrane spinning solution for electrospinning. Then, replace 4 10 mL syringes and draw 5 mL of basement membrane spinning solution for secondary spinning to obtain electrospun fiber membrane. The electrospinning process should always be maintained in a closed environment at 25°C and 40±2% relative humidity. The distance between the needle and the receiver is 20 cm, and the injection speed is 0.10 mm min. -1 , receiving speed is 30 r min -1 The needle tip and ground collector are applied with high voltages of +20kV and -5kV respectively.

[0028] Step 3: The fiber membrane obtained in step 2 is sandwiched between two glass plates, fixed with clips on all sides of the glass plates, and treated under hot pressing at 160°C and 3 MPa for 1 h to obtain a base membrane.

[0029] Step 4: Preparation of amino-functionalized carbon nanotubes: First, 2 g of carbon nanotubes (CNTs) were immersed in 1 mol L -1 The CNTs were acidified in a hydrochloric acid solution for 24 hours, then washed several times with ethanol and dried under vacuum. One gram of the treated CNTs was added to 100 mL of toluene solvent along with 0.5 mL of 3-aminopropyltriethoxysilane (APTES) and allowed to react under reflux for 3 hours. After the reaction, the product was washed with ethanol and dried under vacuum to obtain amino-functionalized carbon nanotubes (CNT-NH2).

[0030] Step 5: Synthesis of S-TpPa@CNT: Tp (21 mg, 0.1 mmol), Pa-SO3H (28 mg, 0.15 mmol), and CNT-NH2 (40 mg) were placed in a Pyrex tube. A 1:1 (v / v) n-butanol / o-dichlorobenzene mixture (2 mL) and 6 M acetic acid (0.2 mL) were added. The mixture was sonicated for 30 minutes, then rapidly frozen in liquid nitrogen and degassed by three freeze-pump-thaw cycles. The tube was sealed and reacted at 120°C for 3 days. After completion of the reaction, the precipitated product was collected by filtration, washed sequentially with dimethylacetamide and acetone, and Soxhlet extracted with tetrahydrofuran for 24 hours. The final product was dried in vacuo at 60°C for 24 hours to obtain S-TpPa@CNT as a dark red powder.

[0031] Step 6: Synthesis of S-TpPa@CNT-Co: The pre-synthesized S-TpPa@CNT (50 mg) was dispersed in 30 mL of anhydrous dichloromethane (CH2Cl2) and thoroughly dispersed by sonication for 10 min. Cobalt acetate (Co(CH3COO)2, 0.06 g, 0.27 mmol) was then added, and the mixture was stirred at room temperature for 24 h. After completion of the reaction, the solid product was collected by vacuum filtration and repeatedly washed with dichloromethane (3 × 10 mL) and ethanol (3 × 10 mL) to completely remove uncoordinated metal salts and organic residues. The resulting deep red solid product was vacuum dried at 40°C for 12 h to obtain the target composite material, S-TpPa@CNT-Co.

[0032] Step 7: Prepare a MXene dispersion loaded with catalytic properties: First, weigh 1.25 mg of MXene and add it to 50 mL of ultrapure water, and ultrasonically disperse it for 15 minutes. Then, add 2 mg of the final product of step 6 and stir it for 1 hour. Ultrasonicate for 60 minutes to uniformly disperse it to obtain a MXene dispersion with catalytic properties.

[0033] Step 8: The two-dimensional layered material dispersion in step 7 is vacuum filtered onto the base film obtained in step 3 under a negative pressure of 0.75 MPa to obtain a composite film.

[0034] Step 9: Weigh 250 mg L -1 5 mL of the concentrated graphene oxide dispersion was vacuum filtered onto the composite membrane described in step eight under a negative pressure of 0.75 MPa, and then placed in a forced air drying oven at 100°C for 60 min to obtain a membrane with a salt-contamination gradient separation catalytic evaporation structure.

[0035] The salt-contamination gradient separation-catalysis-evaporation membrane prepared in this example was used to distill high-salinity wastewater containing 20 ppm aniline. The parameters were set as feed side temperature of 60°C, permeate side temperature of 40°C, and flow rate of 240 mL min. -1 The volume of water collected per minute on the distillation side was recorded using an electronic balance, and the conductivity of the water on the distillation side was monitored using a conductivity meter to record the effluent quality. The composite membrane had a retention rate of up to 98.17% for high-salinity wastewater containing 20 ppm of aniline. Example 3

[0036] This embodiment provides a method for preparing a catalytic evaporation membrane with a salt-contamination gradient separation function, the method comprising the following steps: Step 1: Prepare base membrane spinning solution: weigh 60 g of N,N-dimethylacetamide, then weigh 10 g of polyethersulfone, add the above solvent, heat in a water bath at 80°C and stir until mixed, to obtain a solution as the base membrane spinning solution, and obtain the base membrane spinning solution.

[0037] Step 2: Take 4 10 mL syringes and draw 10 mL of basement membrane spinning solution for electrospinning. Then, replace 4 10 mL syringes and draw 5 mL of basement membrane spinning solution for secondary spinning to obtain electrospun fiber membrane. The electrospinning process should always be maintained in a closed environment at 25°C and 40±2% relative humidity. The distance between the needle and the receiver is 20 cm, and the injection speed is 0.10 mm min. -1 , receiving speed is 30 r min -1 The needle tip and ground collector are applied with high voltages of +20kV and -5kV respectively.

[0038] Step 3: The fiber membrane obtained in step 2 is sandwiched between two glass plates, fixed with clips on all sides of the glass plates, and treated under hot pressing at 160°C and 3 MPa for 1 h to obtain a base membrane.

[0039] Step 4: Preparation of amino-functionalized MXene: First, 2 g of MXene was immersed in 1 mol L -1 The MXene was acidified in a hydrochloric acid solution for 24 hours, then washed several times with ethanol and dried under vacuum. One gram of the treated MXene was added to 100 mL of toluene solvent along with 0.5 mL of 3-aminopropyltriethoxysilane (APTES) and allowed to react under reflux for 3 hours. After the reaction, the product was washed with ethanol and dried under vacuum to obtain the amino-functionalized MXene.

[0040] Step 5: Synthesis of S-TpPa@MXene: Tp (21 mg, 0.1 mmol), Pa-SO3H (28 mg, 0.15 mmol), and amino-functionalized MXene (40 mg) were placed in a Pyrex tube. A 1:1 (v / v) n-butanol / o-dichlorobenzene mixture (2 mL) and 6 M acetic acid (0.2 mL) were added. The mixture was sonicated for 30 minutes, then rapidly frozen in liquid nitrogen and degassed by three freeze-pump-thaw cycles. The tube was sealed and reacted at 120°C for 3 days. After the reaction, the precipitated product was collected by filtration, washed sequentially with dimethylacetamide and acetone, and Soxhlet extracted with tetrahydrofuran for 24 hours. The final product was dried in vacuo at 60°C for 24 hours to obtain S-TpPa@MXene as a dark red powder.

[0041] Step 6: Synthesis of S-TpPa@MXene-Co: The pre-synthesized S-TpPa@MXene (50 mg) was dispersed in 30 mL of anhydrous dichloromethane (CH2Cl2) and ultrasonicated for 10 min to fully disperse it. Cobalt acetate (Co(CH3COO)2, 0.06 g, 0.27 mmol) was then added, and the mixture was stirred at room temperature for 24 h. After the reaction was complete, the solid product was collected by vacuum filtration and repeatedly washed with dichloromethane (3 × 10 mL) and ethanol (3 × 10 mL) to completely remove uncoordinated metal salts and organic residues. The resulting dark red solid product was vacuum dried at 40°C for 12 h to obtain the target composite material, S-TpPa@MXene-Co.

[0042] Step 7: Prepare a molybdenum disulfide dispersion with catalytic properties: First, weigh 1.25 mg of molybdenum disulfide and add it to 50 mL of ultrapure water, and ultrasonically disperse it for 15 minutes. Then, add 2 mg of the final product of step 6 and stir it for 1 hour. Ultrasonicate for 60 minutes to uniformly disperse it to obtain a molybdenum disulfide dispersion with catalytic properties.

[0043] Step 8: The molybdenum disulfide dispersion with catalytic properties in step 7 is vacuum filtered onto the base membrane obtained in step 3 under a negative pressure of 0.75 MPa to obtain a composite membrane.

[0044] Step 9: Weigh 250 mg L -1 5 mL of the concentrated graphene oxide dispersion was vacuum filtered onto the composite membrane described in step eight under a negative pressure of 0.75 MPa, and then placed in a forced air drying oven at 100°C for 60 min to obtain a membrane with a salt-contamination gradient separation catalytic evaporation structure.

[0045] The membrane with salt-contamination gradient separation-catalysis-evaporation structure prepared in this example was used to distill high-salinity wastewater containing 20 ppm aniline. The membrane distillation parameters were set as feed side temperature of 60°C, permeate side temperature of 40°C, and flow rate of 240 mL min -1 The volume of water collected per minute on the distillation side was recorded using an electronic balance, and the conductivity of the water on the distillation side was monitored using a conductivity meter to record the effluent quality. The composite membrane had a retention rate of up to 98.34% for high-salinity wastewater containing 20 ppm of aniline.

Claims

1. A composite membrane with salt-pollution gradient separation and catalytic evaporation functions, characterized in that The composite membrane comprises a separation layer, a catalytic layer and an evaporation layer from top to bottom, wherein the evaporation layer is an electrostatic spinning fiber membrane, the catalytic layer is an organic-inorganic composite thin film, and the separation layer is an organic or inorganic layer.

2. A method for preparing a composite membrane having salt-pollution gradient separation and catalytic evaporation functions according to claim 1, characterized in that The method comprises the following steps: Step 1: adding a hydrophobic polymer to a solvent, heating and stirring in a water bath, and then gradually cooling to room temperature to obtain a base membrane spinning solution, and preparing an electrospun fiber membrane by continuously electrospinning the base membrane spinning solution, wherein: the mass ratio of the hydrophobic polymer to the solvent is 5-20:100; Step 2: sandwiching the electrospun fiber membrane in step 1 between two glass plates and treating it under hot pressing at 100-200°C and 1-5 MPa for 1-6 hours to obtain a base membrane; Step 3: preparing an amino-functionalized one-dimensional tubular or two-dimensional sheet material: immersing 1-3 g of the one-dimensional tubular or two-dimensional sheet material in a hydrochloric acid solution for 12-36 hours, washing and drying, then adding the one-dimensional tubular or two-dimensional sheet material and 3-aminopropyltriethoxysilane to a solvent and refluxing for 2-4 hours, washing and drying to obtain an amino-functionalized one-dimensional tubular or two-dimensional sheet material, wherein the mass volume ratio of the amino-functionalized one-dimensional tubular or two-dimensional sheet material to 3-aminopropyltriethoxysilane is 1-5 g:1-5 mL; Step 4: Preparing an S-TpPa@amino-functionalized one-dimensional tubular or two-dimensional sheet material heat-resistant glass tube: placing the amino-functionalized one-dimensional tubular or two-dimensional sheet material prepared in step 3 together with trialdehyde phloroglucinol and 2,5-diaminobenzenesulfonic acid in a solvent for ultrasonic treatment, degassing, and reacting at 100-200°C for 2-4 days, then filtering and collecting the precipitated product, washing, and Soxhlet extraction, and drying the product to obtain an S-TpPa@amino-functionalized one-dimensional tubular or two-dimensional sheet material heat-resistant glass tube, wherein: the molar concentration ratio of the amino-functionalized one-dimensional tubular or two-dimensional sheet material, Tp, and Pa-SO3H is 0.2-2:1:1-2; Step 5: Preparation of S-TpPa@amino-functionalized one-dimensional tubular or two-dimensional sheet material-Co: The product of step 4 is ultrasonically placed in anhydrous dichloromethane, followed by addition of cobalt acetate and stirring. After the reaction, the solid is collected by suction filtration and repeatedly washed with dichloromethane and ethanol to completely remove uncoordinated metal salts and organic residues. The solid is vacuum dried to obtain the final product S-TpPa@amino-functionalized one-dimensional tubular or two-dimensional sheet material-Co, wherein the ratio of the S-TpPa@amino-functionalized one-dimensional tubular or two-dimensional sheet material, anhydrous dichloromethane and cobalt acetate is 50-100 mg: 20-50 mL: 50-70 mg; Step 6: Prepare a dispersion of one-dimensional tubular or two-dimensional sheet materials loaded with catalytic properties: Weigh 1-20 mg of the one-dimensional tubular or two-dimensional sheet material, add it to ultrapure water and disperse it ultrasonically, then add 50-100 mg of the final product of step 5, stir it, and then disperse it ultrasonically to obtain a dispersion of the one-dimensional tubular or two-dimensional sheet material with catalytic properties; Step 7: vacuum filter the solution in step 6 onto the base membrane obtained in step 2 under a negative pressure of 0.75-2 MPa to obtain a catalytic layer; Step 8: 5-20 mL of a 100-1000 ppm one-dimensional tubular or two-dimensional sheet material dispersion is vacuum filtered onto the catalytic layer obtained in step 7 under a negative pressure of 0.75-2 MPa, and then dried in a forced air drying oven to obtain a separation-catalysis-evaporation sequence membrane.

3. The method for preparing a composite membrane having salt-pollution gradient separation and catalytic evaporation functions according to claim 2, characterized in that In the step 1, the hydrophobic polymer is one or more of polyvinylidene fluoride, polyethersulfone, and polyurethane; the solvent is one or more of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone; the water bath heating temperature is 60-150°C, and the stirring time is 3-5 h; the continuous electrospinning process requires transferring 4 needles of 5-15 mL of spinning solution to the electrospinning machine, and electrospinning is performed in a closed environment at 20-30°C and 35-75% relative humidity, the needle tip and the ground collector are respectively positively and negatively voltageed, the positive voltage is 10-40 kV, the negative voltage is 0-10 kV, the distance between the needle tip and the receiver is 10-30 cm, and the injection speed is 0.1-0.2 mm min -1 , receiving speed is 30~50 r min -1 After the spinning solution is sprayed, the prepared membrane is peeled off from the aluminum foil to obtain the electrospun fiber membrane.

4. The method for preparing a composite membrane having salt-pollution gradient separation and catalytic evaporation functions according to claim 3, characterized in that A conductive agent is further added to the solvent, and the mass ratio of the conductive agent to the hydrophobic high molecular polymer is 0.1-0.5:100; the conductive agent is one or more of lithium chloride, sodium chloride and calcium chloride.

5. The method for preparing a composite membrane having salt-pollution gradient separation and catalytic evaporation functions according to claim 2, characterized in that In step 3, the concentration of the hydrochloric acid solution is 1-3 mol L -1 ; The solvent is toluene.

6. The method for preparing a composite membrane having salt-pollution gradient separation and catalytic evaporation functions according to claim 2, characterized in that In step 4, the one-dimensional tubular material is a carbon nanotube; the two-dimensional sheet material is graphene oxide, MXene, molybdenum disulfide or other two-dimensional sheet materials; the ultrasonic treatment time is 20 to 60 minutes; the number of degassing times is 2 to 4 times; the drying temperature is 40 to 80° C. and the time is 12 to 36 hours; and the solvent is one or more of a mixed solvent of n-butanol, isopropanol, acetic acid, and o-dichlorobenzene.

7. The method for preparing a composite membrane having salt-pollution gradient separation and catalytic evaporation functions according to claim 2, characterized in that In step 5, the one-dimensional tubular material is a carbon nanotube; the two-dimensional sheet material is graphene oxide, MXene, molybdenum disulfide or other two-dimensional sheet materials; the stirring time is 12 to 36 hours; and the vacuum drying temperature is 30 to 60° C. and the time is 10 to 20 hours.

8. The method for preparing a composite membrane having salt-pollution gradient separation and catalytic evaporation functions according to claim 2, characterized in that In step six, the one-dimensional tubular material is a carbon nanotube; the two-dimensional sheet material is graphene oxide, MXene, molybdenum disulfide or other two-dimensional sheet materials; the ultrasonic dispersion speed is 100-500 rpm, and the time is 5-15 min; the stirring time is 0.5-3 h, and the ultrasonic time is 15-60 min.

9. The method for preparing a composite membrane having salt-pollution gradient separation and catalytic evaporation functions according to claim 2, characterized in that In the step eight, the drying temperature is 60-120° C. and the drying time is 10-60 min.

10. Use of the composite membrane with salt-pollution gradient separation and catalytic evaporation functions according to claim 1 in the treatment of complex high-salt wastewater.